The ease of transaction and e-service quality of e-commerce platform on online purchasing decision - Cynthia Hartono; Yunita Budi Rahayu Silintowe; Andrian Dolfriandra Huruta (BISMA (Bisnis dan Manajemen), 2021)
Online business development ease consumers to make purchases. One marketplace that can be consumer choice to shop online is Akulaku. Online purchasing decisions at Akulaku can be influenced by various factors such as ease of transaction and e-service quality. This study aims to analyze the effect of ease of transaction and e-service quality on online purchasing decisions in Akulaku. A total of 104 Akulaku consumers lived across Indonesia as samples were collected by a purposive sampling technique. The data was collected using an online questionnaire with structured questions given to Akulaku consumers. The data were analyzed using multiple regression. The results indicate that the ease of transaction has a positive influence on online purchasing decisions in Akulaku. Besides, the e-service quality also has a positive influence on the online purchasing decisions in Akulaku.